The transmission mechanism of monetary policy in the Jamaican economy ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1997)
Attempts to assess the channels through which monetary policy is transmitted in Jamaica since economic liberalisation.
Keywords: MONETARY POLICY